2011
DOI: 10.1111/j.1467-6419.2011.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Liberalization in Sub‐saharan Africa: What Do We Know?

Abstract: Beginning from the early 1980s countries in Sub-Saharan Africa embarked on financial liberalization policies with a view to reversing the ill-effects of financial repression. This paper provides a survey of financial liberalization in Sub-Saharan African countries over the period 1980 to 2004. Our review of empirical studies showed that financial liberalization has had diverse and contrasting effects on savings, investment and economic growth. Most studies found a significant positive effect of financial liber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…2 These adverse growth effects are consistent with the evidence showing that financial liberalization, to the extent that it is accompanied by greater financial volatility, may not contribute much to promoting growth; see for instance Misati and Nyamongo (2012) and the overview by Fowowe (2013). The latter study, in particular, highlights the need to strengthen prudential regulation to enhance the benefits of financial liberalization.…”
supporting
confidence: 74%
“…2 These adverse growth effects are consistent with the evidence showing that financial liberalization, to the extent that it is accompanied by greater financial volatility, may not contribute much to promoting growth; see for instance Misati and Nyamongo (2012) and the overview by Fowowe (2013). The latter study, in particular, highlights the need to strengthen prudential regulation to enhance the benefits of financial liberalization.…”
supporting
confidence: 74%
“…This suggests that the loose regional integration policies implemented by the ASEAN economies may be effective in the region. Thus, it is suggested that there are important prerequisites that must be in place before financial reforms and integration can be successful, which includes institutional reform, stable macroeconomic environment, policy credibility and effective and adequate monetary supervision (Fowowe 2013). Similarly, recent research has emphasised the role of institutional quality in promoting economic growth in the ASEAN economies (Masron 2017).…”
Section: Countrymentioning
confidence: 99%
“…This section highlights and reviews various financial sector reforms in SSA and the role these reforms have played in augmenting economic growth and boosting investment in the real sector. Fowowe (2013) asserts that most financial systems in SSA countries are still marked by inefficient resource mobilization, high-transaction costs and information asymmetry. For example, credits are disproportionately directed to specific sectors by governments at low-interest rates.…”
Section: The Origin Of Financial Liberalization In Some Selected Ssa mentioning
confidence: 99%
“…These challenges include, amongst others: banking crises, shallow and unstable exchange rates, a widening spread between lending and deposit rates and a drastic decline or stagnation of the domestic credit to financial depth. A number of studies (Brownbridge, 1998;Daumont, Le Gall, & Leroux, 2004;Fowowe, 2013;Ikhide, 2015;Misati & Nyamongo, 2012) show that systemic banking crises occurred in many SSA countries [for example, Cameroon (1988[for example, Cameroon ( -1991, Nigeria (1991Nigeria ( -1995, Ghana (1982Ghana ( -1989 and Kenya (1993Kenya ( -1995] immediately after they had implemented financial liberalization policies. Misati and Nyamongo (2012) believe that financial liberalization policies are still one of the most controversial policies because of its negative impact on the relationship between financial development and economic growth.…”
Section: Introductionmentioning
confidence: 99%